Hepatitis C Virus Epidemiology in Djibouti, Somalia, Sudan, and Yemen: Systematic Review and Meta-Analysis. - Karima Chaabna; Silva P Kouyoumjian; Laith J Abu-Raddad (PLoS ONE, 2016)
Objectives To characterize hepatitis C virus (HCV) epidemiology and assess country-specific population-level HCV prevalence in four countries in the Middle East and North Africa (MENA) region: Djibouti, Somalia, Sudan, and Yemen. Methods Reports of HCV prevalence were systematically reviewed as per PRISMA guidelines. Pooled HCV prevalence estimates in different risk populations were conducted when the number of measures per risk category was at least five. Results We identified 101 prevalence estimates. Pooled HCV antibody prevalence in the general population in Somalia, Sudan and Yemen was 0.9% (95% confidence interval [95%CI]: 0.3%-1.9%), 1.0% (95%CI: 0.3%-1.9%) and 1.9% (95%CI: 1.4%-2.6%), respectively. The only general population study from Djibouti reported a prevalence of 0.3% (CI: 0.2%-0.4%) in blood donors. In high-risk populations (e.g., haemodialysis and haemophilia patients), pooled HCV prevalence was 17.3% (95%CI: 8.6%-28.2%) in Sudan. In Yemen, three studies of haemodialysis patients reported HCV prevalence between 40.0%-62.7%. In intermediate-risk populations (e.g.. healthcare workers, in patients and men who have sex with men), pooled HCV prevalence was 1.7% (95%CI: 0.0%-4.9%) in Somalia and 0.6% (95%CI: 0.4%-0.8%) in Sudan. Conclusion National HCV prevalence in Yemen appears to be higher than in Djibouti, Somalia, and Sudan as well as most other MENA countries; but otherwise prevalence levels in this subregion are comparable to global levels. The high HCV prevalence in patients who have undergone clinical care appears to reflect ongoing transmission in clinical settings. HCV prevalence in people who inject drugs remains unknown.